Primary leiomyosarcoma of the lung - Ramanathan, T. (1974)
Ramanathan, T. (1974).Thorax, 482-489. Primary leiomyosarcoma of the lung. Three new cases of primary leiomyosarcoma of the lung are presented. The relevant literature has been reviewed. The similarity in the clinical features between bronchogenic carcinoma and leiomyosarcoma is emphasized. The only distinctive feature of leiomyosarcoma is the absence of lymph node involvement.